Electrospinning of Flexible Poly(vinyl alcohol)/MXene Nanofiber-Based Humidity Sensor Self-Powered by Monolayer Molybdenum Diselenide Piezoelectric Nanogenerator - Wang, Dongyue; Zhang, Dongzhi; Li, Peng; Yang, Zhimin; Mi, Qian; Yu, Liandong (Nano-Micro Letters, 2021)
Two-dimensional material has been widely investigated for potential applications in sensor and flexible electronics. In this work, a self-powered flexible humidity sensing device based on poly(vinyl alcohol)/Ti3C2Tx (PVA/MXene) nanofibers film and monolayer molybdenum diselenide (MoSe2) piezoelectric nanogenerator (PENG) was reported for the first time. The monolayer MoSe2-based PENG was fabricated by atmospheric pressure chemical vapor deposition techniques, which can generate a peak output of 35 mV and a power density of 42 mW m−2. The flexible PENG integrated on polyethylene terephthalate (PET) substrate can harvest energy generated by different parts of human body and exhibit great application prospects in wearable devices. The electrospinned PVA/MXene nanofiber-based humidity sensor with flexible PET substrate under the driven of monolayer MoSe2 PENG, shows high response of ∼40, fast response/recovery time of 0.9/6.3 s, low hysteresis of 1.8% and excellent repeatability. The self-powered flexible humidity sensor yields the capability of detecting human skin moisture and ambient humidity. This work provides a pathway to explore the high-performance humidity sensor integrated with PENG for the self-powered flexible electronic devices. Highlights: 1 A flexible piezoelectric nanogenerator (PENG) based on 2D single-layer MoSe2 flake on polyethylene terephthalate was fabricated. 2 A high-performance flexible poly(vinyl alcohol)/MXene (PVA/MXene)-based humidity sensor was fabricated by electrospinning. 3 The PVA/MXene composite-based humidity sensor was self-powered by MoSe2 PENG and exhibited excellent properties.